HIV information needs of transgender people and their healthcare providers. Issue 3 (4th March 2019) - Uhrig, Jennifer D.; Stryker, Jo Ellen; Bresee, Sara; Gard Read, Jennifer; Parvanta, Sarah; Ruiz, Francisco; DeLuca, Nickolas
ABSTRACT: Despite the disproportionate burden of HIV among transgender people in the United States, few HIV-related communication materials exist for transgender people or their healthcare providers. Our goal was to understand the barriers and facilitators transgender people face in accessing HIV prevention, testing, and care services and the potential implications for message development and dissemination. We reviewed the literature and interviewed nine key informants representing healthcare and service providers, researchers, and transgender advocates. Healthcare providers who care for transgender patients often demonstrate a lack of transgender competent care strategies. In addition, transgender people face many barriers to accessing HIV services. Although communication materials cannot address many of these barriers, materials specifically developed for transgender people and their healthcare providers would fill a gap and may increase uptake of HIV services. Materials for transgender people should include gender-affirming messaging and imagery, be framed in terms of resiliency, and present HIV information tailored to the needs of transgender people. Materials for healthcare providers should provide basic information to increase transgender competency and provision of comprehensive healthcare for transgender patients, inclusive of gender-affirming and HIV prevention, testing and care services. Channels for disseminating materials to transgender people and healthcare providers are described.